HTTP blocking in MM: signal.org, twitter.com, whatsapp.com (Myanmar) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Myanmar. Data sourced from CensoredPlanet.
Censorship Incident ID: MM-2026-0007. Severity: warning. Confidence: 85%